Marketing Management and Financial Management of Goat Farming in Bantar Panjang Village, Tigaraksa, Tangerang Regency - Arifin Idrus; Mariana Tenreng; Slamet Riyanto; Susilowati Susilowati (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to analyze the marketing management and financial management of goat farming in Bantar Panjang Village, Tigaraksa District, Tangerang Regency. Goat farming is one of the main sources of income for the local community, yet it still faces challenges in marketing and effective financial record-keeping. The research method used is a descriptive qualitative approach through interviews, field observations, and document studies with local farmers. The findings show that the marketing strategy is still conventional, relying on local networks, while financial record-keeping is not well-structured, making it difficult to make long-term economic decisions. The study recommends the implementation of a digital marketing strategy, enhancing the farmers' capacity in business management, and using a simple but systematic financial recording system to improve the efficiency and sustainability of the goat farming business.